Pure and Applied Chemistry:stucture based nomenclature for cyclic organic macromolecules - Guide to IUPAC (new york, 2007)
Official journal of the international union of pure and applied chemistry
Vol.88,No.2,February2008
Keywords: Chemistry; Organic Chemistry